Bloom of the flower dragon - West, Tracey, 1965-; Howells, Graham (2022)
Drake and the other Dragon Masters help Wildroot, a Flower Dragon whose home is in danger, find his Dragon Master Oskar after Oskar's identity is revealed to them by the Dragon Stone.
Ages 6-8.
Grades 2-3.
Keywords: Dragons -- Fiction; Magic -- Fiction; Wizards -- Fiction; Adventure and adventurers -- Fiction; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / Action & Adventure / General; Novels